A 2020 perspective on “Spreading the word : how customer experience in a traditional retail setting influences consumer traditional and electronic word-of-mouth intention” (2020)
The convergence of the brick and mortar and online worlds is now more prominent than ever. It is becoming increasingly difficult to operate exclusively in one of these two environments. While physical stores provide retailers with a unique opportunity to deliver unique in-store experiences that can also leverage their online features, online retailers are also establishing a presence in the physical world to supplement the experience offered online. Therefore, understanding how consumers behave in each of these environments and how these behaviors are expressed across both worlds has become increasingly important to marketers managing omnichannel operations. Only by providing a complete experience to the consumer from all possible contact points will retailers be able to achieve their omnichannel goals.